STEM-Based Global Warming E-Book in Sustainable Development Based on Gender View - Aswirna, Prima; Aldila, Endang; Nurhasnah, Nurhasnah; Fahmi, Reza (Universitas Islam Negeri Raden Intan Lampung, 2022)
Gender has become a critical issue globally because it is one of the main goals of global collective transformation in sustainable development. This research is motivated by the absence of science teaching materials with STEM-based global warming material with the principle of sustainable development in terms of gender perspective. The purpose of this research is to develop and produce a STEM-based e-book with sustainable development principles based on gender that is valid, practical, and effective. This research is a Research and Development using the Plomp model which consists of 3 stages, namely the initial research stage, the development stage, and the assessment stage. The results showed that the STEM-based e-book with gender-based sustainable development principles obtained a validity test result of 85.85%, a practicality test result of 87.16%, and an effective test result for female students of 83, 5% while for male students is 80%. So, it can be concluded that e-books are very valid, very practical, and very effective for use in classroom learning.